Pengaruh Kinerja Keuangan, Ukuran Dewan Pengawas Syariah, dan Ukuran Perusahaan terhadap Jumlah Zakat Entitas Bank Umum Syariah di Indonesia - Fadhillah, Rizky; Atibah (P3M Politeknik Negeri Banjarmasin, 2022)
The research aims to analyze the effect of financial performance (ROA and CAR), the size of the Sharia Supervisory Board, and the company size on the amount of entity zakat in Sharia Commercial Banks (BUS) in Indonesia. This research used a correlative quantitative method with the analysis technique of multiple linear regressions. The data used is secondary data sourced from the BUS annual financial statements for the 2015-2020 periods. This study used a purposive sampling technique obtained from five BUS samples. The results show that partially, ROA and company size have a positive effect on the amount of entity zakat, whereas CAR and the size of the Sharia Supervisory Board do not affect the number of zakat entities. Forward, it simultaneously shows that the financial performance as proxied by ROA and CAR, the size of the Sharia Supervisory Board, and the company size have a positive effect on the amount of entity zakat. The coefficient of determination of Adjusted R Square shows a result of 0.798 which means that ROA, CAR, size of the Sharia Supervisory Board, and company size have an influence on the amount of entity zakat by 79.8% and the remaining 20.2% influenced by other variables outside the research model. It indicates that this research model is representative in explaining the variables that affect the amount of entity zakat in BUS because the Adjusted R Square value is more than 50%.